Solid State Physics : Problems and Solutions - Mihaly, Laszlo; Martin, Michael C (Weinheim : Wiley-VCH, 2009)
The ideal supplement to the standard texts in condensed matter physics Solving homework problems is the single most effective way for students to familiarize themselves with the language and details of solid state physics. Testing problem-solving ability is the best means at the professor's disposal for measuring student progress at critical points in the learning process. This book enables any instructor to supplement end-of-chapter textbook assignments with a large number of challenging and engaging practice problems and discover a host of new ideas for creating exam questions. Designed to be used in tandem with any of the excellent textbooks on this subject, Solid State Physics: Problems and Solutions provides a self-study approach through which advanced undergraduate and first-year graduate students can develop and test their skills while acclimating themselves to the demands of the discipline. Each problem has been chosen for its ability to illustrate key concepts, properties, and systems, knowledge of which is crucial in developing a complete understanding of the subject, including: Crystals, diffraction, and reciprocal lattices. Phonon dispersion and electronic band structure. Density of states. Transport, magnetic, and optical properties. Interacting electron systems.
References 305-306p.; Index 307-315p.
Keywords: Solid state physics; Physics